Source–sink dynamics shapes the spatial distribution of soil protists in an arid shrubland of northern Chile. (February 2015) - Fernández, Leonardo D.
Abstract: Arid shrublands are spatially heterogeneous environments composed of shrubs patches surrounded by a matrix of bare soil. In this biome, bare soils harbor fewer protist species than soils covered by shrubs because they represent low quality habitats for most of them. Furthermore, protist species composition in bare soils often represents a subset of that found in soils covered by shrubs. This pattern suggests that the variability in protist species composition is the result of a non-random mechanism. I performed a nested analysis to test the hypothesis that the source–sink dynamics is shaping the spatial distribution of soil testate amoebae (a polyphyletic group of protists) in an arid shrubland of northern Chile. I found that assemblages of soil testate amoebae are significantly nested in this biome. The species-poor assemblages inhabiting bare soils are thus, only a subset of species-rich assemblages located in vegetated soils. This nested pattern may be the result of a colonization–extinction tradeoff characterized by species-poor bare soils acting as 'sinks' maintained by the permanent colonization of individuals coming from species-rich vegetated soils acting as 'sources'. Thus, the source–sink dynamics represents a valid conceptual framework to explain the spatial patterns of soil protists distribution in arid shrublands. Highlights: A source–sink dynamics shaping protist distribution in arid shrubland is proposed. Bare soils harbor fewer protist species than vegetated soils in this biome. Species composition in bare soils was a subset of that found in vegetated soils. Bare soils acted as 'sink' habitats and vegetated soils as 'source' habitats.